A Review of Eye Movement Desensitization and Reprocessing (EMDR): Research Findings and Implications for Counsellors - MacCluskie, Kathryn C. (Canadian Journal of Counselling and Psychotherapy, 2007)
The last six years have seen the emergence of a new therapeutic technique, most often used to treat symptoms of post traumatic stress disorder (PTSD), called Eye Movement Desensitization and Reprocessing (EMDR) (Shapiro 1989a, 1989b, 1991,1995). A numberof uncontrolled case studies followed the initial studies of EMDR alleging remarkable successes in the treatment of PTSD. More recently, controlled studies examining the efficacy of this strategy have appeared, most often in the behavioural literature. Considerable variability exists in the findings of the controlled studies, making definitive conclusions difficult to achieve. This article examines the strengths and weaknesses of the published studies, illuminates the nature of the debate about efficacy of EMDR, and reviews implications for practicing counsellors and counsellor trainees.